Truth in many tongues: religious conversion and the languages of the early Spanish Empire - Wasserman-Soler, Daniel I. (Penn State University Press, 2020)
Intro -- Half Title Page -- Title Page -- Copyright -- Dedication -- Contents -- List of Illustrations -- Acknowledgments -- Note on the Text -- Introduction -- 1 / The Spanish Language and the Inquisition, ca. 1550-1600 -- 2 / Arabic and Spanish in Granada, ca. 1492-1570 -- 3 / Arabic and Romance in Valencia, ca. 1540-1600 -- 4 / Native Tongues and Spanish in New Spain, ca. 1520-85 -- 5 / Creating a Multilingual New Spain, ca. 1550-1600 -- Conclusion -- Appendix: Linguistic Abilities of Franciscan Friars in Sixteenth-Century New Spain -- Notes -- Bibliography -- Index.